2022
DOI: 10.1021/acsami.2c09551
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of Rational Separator Microstructures in Guiding Dendrite Growth and Reviving Dead Li

Abstract: Li metal has attracted considerable attention as the preferred anode material for high-energy batteries. However, Li dendrites have limited the development of Li-metal batteries. Herein, the effects of tuning the porous separator microstructure (SM) for guiding Li dendrite growth and reviving dead Li are revealed using a mechano-electrochemical phase-field model. A strategy of guiding, instead of suppression, was applied to avoid disordered Li dendrite growth. By analyzing the effects of the number of layers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…While we do not currently have the computational capabilities to address this, it presents an important aspect of CPE design where microstructure, in addition to conductivity and mechanical strength, should be a primary focus for creating high efficiency solid-state lithium metal batteries. Gao et al recently reported design rules for separator porosity, spacing, and thickness to limit dendrite propagation and dead lithium formation; we believe that these can be applied to Li + -conducting nanofiber structures in CPEs as well. Our results also show that it is important to prevent dendrites from forming in the first placebulk microstructure may slow dendrite growth, but only a strong and homogeneous electrode–electrolyte interface can ensure safe lithium metal cycling in the long term.…”
Section: Results and Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…While we do not currently have the computational capabilities to address this, it presents an important aspect of CPE design where microstructure, in addition to conductivity and mechanical strength, should be a primary focus for creating high efficiency solid-state lithium metal batteries. Gao et al recently reported design rules for separator porosity, spacing, and thickness to limit dendrite propagation and dead lithium formation; we believe that these can be applied to Li + -conducting nanofiber structures in CPEs as well. Our results also show that it is important to prevent dendrites from forming in the first placebulk microstructure may slow dendrite growth, but only a strong and homogeneous electrode–electrolyte interface can ensure safe lithium metal cycling in the long term.…”
Section: Results and Discussionmentioning
confidence: 94%
“…Lithium deposition with separators having pores parallel to the electrode surface, analogous to aligning nanofibers in planes against the electrode, is predicted to control dendrite formation and even revive dead lithium depending on the separator dimensions. 68 Recent computational modeling predicted that ceramic ordering at the lithium metal interface in composites can lead to heterogeneous lithium plating due to uneven Li + transport, and that a polymer interlayer at the interface�as fabricated from our composite production process�is one solution to this issue for even lithium plating. 74 Keeping in mind these nuances of inherently heterogeneous CPEs, any significant benefits from ionic conductivity and dictated lithium deposition should lead to more homogeneous, dense lithium deposits that should be easily stripped on discharge.…”
Section: Effect Of Fiber Loading On Ce and Ccd Our Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Rapid depletion of Li by means of “dead” Li and unstable SEI makes the LMA inadequate to supply Li + loss of the LCO cathode during cycling, leading to the decrease of the total capacity . When the Li anode has excessive Li + content, the capacity of the full cell still has a fast downtrend (30.7%, 250th), which should be ascribed to severe polarization caused by stacking “dead Li” and thick SEI. , By contrast, there is an obvious increase in the capacity retention for LPNF@Li||LCO; it delivers an 80.8% capacity retention after 250 cycles. In consideration of the confined capacity ratio, LPNF can effectively inhibit the growth of Li dendrites and then stabilize interface reactions between the Li metal and the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Once charging begins, the electrochemical reaction of Li + + e – → Li occurs, leading to dendrite growth. In our previous work, , many detailed descriptions of the behavior evolution of dendrites were provided during the charging process. On the contrary, once the discharge begins, the dendrites begin to undergo dissolution reactions, Li → Li + + e – .…”
Section: Electrochemomechanical Pfmmentioning
confidence: 99%